2017
DOI: 10.1016/s2214-109x(17)30298-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of hepatitis D virus infection in sub-Saharan Africa: a systematic review and meta-analysis

Abstract: SummaryBackgroundHepatitis D virus (also known as hepatitis delta virus) can establish a persistent infection in people with chronic hepatitis B, leading to accelerated progression of liver disease. In sub-Saharan Africa, where HBsAg prevalence is higher than 8%, hepatitis D virus might represent an important additive cause of chronic liver disease. We aimed to establish the prevalence of hepatitis D virus among HBsAg-positive populations in sub-Saharan Africa.MethodsWe systematically reviewed studies of hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
112
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 55 publications
13
112
2
2
Order By: Relevance
“…The prevalence of HDV reported in the present study is concordant with results from a recent systematic review where pooled HDV seroprevalence ranged from 7.3% (CI 3.5–12.2) in the general population to 9.6% (CI 2.3–20.4) in liver‐disease population across West Africa . Interestingly, marked differences in HDV prevalence were reported according to countries.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of HDV reported in the present study is concordant with results from a recent systematic review where pooled HDV seroprevalence ranged from 7.3% (CI 3.5–12.2) in the general population to 9.6% (CI 2.3–20.4) in liver‐disease population across West Africa . Interestingly, marked differences in HDV prevalence were reported according to countries.…”
Section: Discussionsupporting
confidence: 91%
“…This could partly explain the geographical distribution of HDV 5. Whereas the risk behaviour of homosexuals will raise the susceptibility of HCV infection,27 HCV coinfection and liver disease are said to be the additional risk factors for HDV infection 28. In our study, patients with liver disease had a higher prevalence than HBsAg carriers (online supplementary appendix figure S2).…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, issues with use of unscreened blood products, unsafe medical procedures and restricted access to antiviral treatments still remain to be solved in poor-resourced countries 1. Studies have shown that the immigrant children have lower immunisation coverage and higher HBV prevalence than native ones, which implies immigrants may have limited access to medical care which is true especially for illegal immigrants 28. More attention is needed to be paid to global HBV vaccination programme, as our result showed that the decline in HDV infection is most likely due to the successful implementation of HBV vaccination programme.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion or exclusion of studies may be justified based on prespecified criteria but even if high standards are applied the outcome of systematic reviews can be surprisingly different. This is also the case here where data for Africa suggested by Chen et al differed from a recent systematic review and meta-analysis focusing on Africa 11. In that study, two publications from Benin and Somalia reporting higher HDV seroprevalences were not considered.…”
mentioning
confidence: 73%